Complex Posterior reversible encephalopathy syndrome with ACA infarct a woman with Lupus: Case Report and Review (2023)
Posterior reversible encephalopathy syndrome is a clinical–radiological disorder, which usually progresses with classical acute neurological symptoms (visual impairment, acute headache, altered level of consciousness, seizures, and even focal neurological deficit). A case presented with a review of the currently available literature is reported in this article.